2007
DOI: 10.1292/jvms.69.471
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bovine Torovirus in Fecal Specimens of Calves with Diarrhea in Japan

Abstract: ABSTRACT. The aim of this study was to determine the prevalence of bovine torovirus (BoTV) in bovine fecal samples and to determine whether a relationship exists between BoTV and diarrhea in Japan. Ninety-nine diarrheic and 114 normal fecal samples from calves in Hokkaido Prefecture and 38 diarrheic fecal samples from calves in 10 other prefectures were examined by reverse transcription (RT)-PCR with primers designed in the spike (S) gene for the presence of BoTV. The specimens were also examined for the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
23
1
2
Order By: Relevance
“…Unlike bovine caliciviruses, it was difficult to judge the role that BToV may play in calf diarrhea because the virus was detected in a relatively small number of the fecal samples examined (1.1%). Such a detection frequency of BToV in our study is similar to what was previously reported from Korea (2.9%) and Austria (5.2%) but different from that reported in USA (36.4%) and Japan (18%) (Duckmanton et al, 1998;Haschek et al, 2006;Kirisawa et al, 2007;Park et al, 2008b). Although a statistically significant association between BToV and diarrhea could not be demonstrated due to a low prevalence, it must be pointed out that the virus was detected only in feces from diarrheic calves.…”
Section: Discussionsupporting
confidence: 82%
“…Unlike bovine caliciviruses, it was difficult to judge the role that BToV may play in calf diarrhea because the virus was detected in a relatively small number of the fecal samples examined (1.1%). Such a detection frequency of BToV in our study is similar to what was previously reported from Korea (2.9%) and Austria (5.2%) but different from that reported in USA (36.4%) and Japan (18%) (Duckmanton et al, 1998;Haschek et al, 2006;Kirisawa et al, 2007;Park et al, 2008b). Although a statistically significant association between BToV and diarrhea could not be demonstrated due to a low prevalence, it must be pointed out that the virus was detected only in feces from diarrheic calves.…”
Section: Discussionsupporting
confidence: 82%
“…Different species and genotypes of cryptosporidia were recorded in brown rats (Rattus norvegicus) in an urban area in western Japan (Kimura et al 2007). Moreover, different incidences of Cryptosporidium were recorded in young calves according to the location of the sampled animals (Kirisawa et al 2007) Although Miyagi prefecture is known as dairy farming areas, very little information is available about cryptosporidiosis as well as its diversity in these areas. Moreover, while the association between cryptosporidiosis and calves is well established, little is known about adult dairy cattle in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…The reported fecal prevalence of BToVs in bovine diarrhea specimens by conventional RT-PCR or nested PCR was 36.4% in Canada (Duckmanton et al, 1998), 5.2% in Austria (Haschek et al, 2006), 9.7% in the United States (Hoet et al, 2003), 3.6% in Hungary (Matiz et al, 2002), 15.2-23.7% in Japan (Kiriwasa et al, 2007) and 2.9% in South Korea (Park et al, 2008). Porcine toroviruses were detected in 5% of the diarrhea specimens of piglets in Hungary (Matiz et al, 2002), 23.7% in Japan (Kiriwasa et al, 2007), and 6.4% in South Korea . Using the same South Korean bovine and porcine fecal samples (Park et al, 2008;Shin et al, 2010), SYBR Green realtime RT-PCR assay detected BToVs in 18.2% and PToVs in 36.0% of the samples.…”
Section: Discussionmentioning
confidence: 99%